2011
DOI: 10.1245/s10434-011-1927-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Right Hepatectomy With Intrahepatic Transection of the Right Bile Duct

Abstract: Laparoscopic major hepatectomy is feasible. As in open hepatectomies, intrahepatic transection of the right bile duct may be safer because there is a decreased risk of injury to the left hepatic duct.4 (,) 5 Larger series with longer-term follow-up are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Tsai et al recently reported on a series of 13 patients undergoing laparoscopic right hepatectomies for malignancy. 49 The conversion rate was 7.7% (one patient) with a mean operative time of 401 minutes and a mean blood loss of 873 mL.…”
Section: Major Hepatectomiesmentioning
confidence: 94%
“…Tsai et al recently reported on a series of 13 patients undergoing laparoscopic right hepatectomies for malignancy. 49 The conversion rate was 7.7% (one patient) with a mean operative time of 401 minutes and a mean blood loss of 873 mL.…”
Section: Major Hepatectomiesmentioning
confidence: 94%
“…[5][6][7][8][9] With increasing experience in laparoscopic liver surgery, the prospect of a laparoscopic approach for the management of ICC can no longer be considered as an extreme or rare procedure. The aim of our study was to determine the feasibility and safety of LLR for ICC and to analyze its clinical and oncologic outcome compared with conventional open liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery for the management of gallbladder cancer may be ideal before attempting formal laparoscopic major hepatectomy. Although it is important to be able to identify the left and right hepatic ducts, extraparenchymal transection may increase the risk of bile duct injury and is now done via intrahepatic transection [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased risk of damaging the contralateral bile duct, and if possible, the left or right hepatic duct is taken with a laparoscopic GIA stapler within the hepatic parenchyma (fig. 5) [19]. …”
Section: Methodsmentioning
confidence: 99%